The role of probiotics in modulation of the gut-brain axis: a prospective therapy for depression and mood disorders - Wang, Hui; Chen, Yining; Zhao, Allen; Shen, Zhongxia; Zhang, Yu (Frontiers in Pharmacology, 2026)
The gut-brain axis is a bidirectional pathway linking the gastrointestinal microbiota to neurological functions. While its significance in the pathogenesis of gastrointestinal conditions is well-documented, emerging evidence indicates that dysbiosis of the gut microbiota could also be implicated in various neuropsychiatric disorders, specifically major depressive disorder (MDD). MDD represents a debilitating illness that accounts for a significant portion of global disability. Although numerous medications have been developed to manage depression, they are frequently plagued by variable efficacy and unpleasant adverse effects. The inconsistency of antidepressant effects highlights the complexity and poorly understood pathophysiology underlying this condition. Recent studies suggest that MDD may involve disruptions in the gut-brain axis via gut dysbiosis, induction of inflammation, metabolic disturbances of neuroactive substances, and dysregulation of the hypothalamic-pituitary-adrenal axis, along with the autonomic and enteric nervous systems. Given the direct and indirect connections between the microbiota and these physiological processes, probiotics are increasingly being explored as a prospective therapeutic option for MDD. Multiple probiotic formulations have shown promise in both preclinical and clinical settings, demonstrating effectiveness in attenuating symptoms associated with MDD. This review provides an overview of the pathophysiologic attributes of MDD, with particular focus on disturbances along the gut-brain axis, and investigates current findings regarding the role of probiotics in addressing these challenges. We conclude by identifying persistent gaps in the literature and proposing directions for future studies.